1997
DOI: 10.1083/jcb.137.5.1001
|View full text |Cite
|
Sign up to set email alerts
|

Insertional Mutation of the Drosophila Nuclear Lamin Dm0 Gene Results in Defective Nuclear Envelopes, Clustering of Nuclear Pore Complexes, and Accumulation of Annulate Lamellae

Abstract: Nuclear lamins are thought to play an important role in disassembly and reassembly of the nucleus during mitosis. Here, we describe a Drosophila lamin Dm0 mutant resulting from a P element insertion into the first intron of the Dm0 gene. Homozygous mutant animals showed a severe phenotype including retardation in development, reduced viability, sterility, and impaired locomotion. Immunocytochemical and ultrastructural analysis revealed that reduced lamin Dm0 expression caused an enrichment of nuclear pore comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
164
1
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(175 citation statements)
references
References 85 publications
(121 reference statements)
8
164
1
1
Order By: Relevance
“…The function of AL is not well understood. Thus far, the only other genetic alteration that is known to promote AL formation is the disruption of the Drosophila nuclear lamin Dm 0 gene (21). Characteristically, lamin Dm 0 -deficient cells form large numbers of cytoplasmic AL, but do not exhibit major changes in the NPC density of their NEs.…”
Section: Discussionmentioning
confidence: 99%
“…The function of AL is not well understood. Thus far, the only other genetic alteration that is known to promote AL formation is the disruption of the Drosophila nuclear lamin Dm 0 gene (21). Characteristically, lamin Dm 0 -deficient cells form large numbers of cytoplasmic AL, but do not exhibit major changes in the NPC density of their NEs.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in levels of lamin Dm 0 activity in Drosophila and elimination of lamin A gene in mouse have both shown to yield abnormalities in the pattern of NPCs (Lenz-Bohme et al, 1997;Harel et al, 1998;Sullivan et al, 1999). We therefore compared the spatial organization of the NPCs in lmn-1 (RNAi) embryos and normal C. elegans embryos by staining them with monoclonal antibody MAb414, which recognizes the FG repeats present in many nucleoporins (Davis and Blobel, 1987).…”
Section: An Intact Nuclear Lamina Is Required For the Correct Spacingmentioning
confidence: 99%
“…These results suggest that the association of the nuclear lamina with the NPCs is required for their correct spacing. The role of the nuclear lamina in spacing NPCs is probably conserved in evolution since similar phenotypes are seen in lines with reduced Drosophila lamin Dm 0 and in mice lacking the lamin A gene (Lenz-Bohme et al, 1997;Harel et al, 1998;Sullivan et al, 1999). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Drosophila, where no cytoplasmic IF genes have been found, there are two nuclear lamin genes, DM 0 and C. Genetic analyses have shown that DM 0 is essential for nuclear organization, and mutations in this gene result in the formation of abnormal nuclear envelopes, nuclear pore clustering, and the accumulation of annulate lamellae, the storage forms of nuclear envelopes. This produces severe defects, including slow developmental progression, sterility, and impaired locomotion (20).…”
Section: Ntermediate Filaments (If) Representmentioning
confidence: 99%